VOCABULARY LEARNING STRATEGIES USED BY STUDENTS IN PRIMARY SCHOOL - Waode Hamsia; Alfa Husnul Hakimah (Proceedings Education and Language International Conference, 2017)
This research aimed to find out the kinds of strategies and the application of the strategies which were used by students in primary school in improving vocabulary learning. Descriptive qualitative was applied as a research method to find out the objective of the research. The techniques of data collection were used in this research were observation and questionnaire. The data analysis used in this research was the interactive model analysis from Miles and Huberman that consists of data reduction, data display, and conclusion. The results showed that there were twenty one kinds of strategies which were used by the students in improving vocabulary. The strategies that were employed by the students mostly were influenced by the teacher’s teaching techniques. The orders of the teacher seemingly become a habit for the student to be conducted automatically in the process of language learning. Keywords: Vocabulary Learning Strategies, Language Learning.